2022
DOI: 10.3989/egeol.44641.614
|View full text |Cite
|
Sign up to set email alerts
|

Prospección minera de la mineralización de óxidos de Fe-Mn-Pb en Jbel Skindis (Alto Atlas Oriental, Marruecos) basada en teledetección y SIG

Abstract: En los últimos años, la teledetección ha ocupado un lugar destacado en los programas de exploración minera dada su utilidad para identificar minerales de alteración, como la arcilla y los hidróxidos. Estos minerales son guías significativas para encontrar depósitos minerales que albergan concentraciones valiosas de metales base. Este trabajo se centra en las mineralizaciones de Fe-Mn-Pb dentro del área de Jbel Skindis consideradas como un zona de estudio para ilustrar la aplicación de imágenes de teledetección… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Based on several previous works such as (Choukrad et al, 2020;Tobi et al, 2022), 657 and 257 color composites as RGB images are useful widely in lithologic mapping, they suggest that clay and carbonate minerals are characteristic of absorption of 2.1 to 2.4 µm and reflectance of 1.55 to 1.75 µm. On the same basis, and after visual examination of several RGB band combinations, we found that the 2, 5 and 7 give good discrimination between limestones, sandstones, and alluviums.…”
Section: Lithology Extraction and Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on several previous works such as (Choukrad et al, 2020;Tobi et al, 2022), 657 and 257 color composites as RGB images are useful widely in lithologic mapping, they suggest that clay and carbonate minerals are characteristic of absorption of 2.1 to 2.4 µm and reflectance of 1.55 to 1.75 µm. On the same basis, and after visual examination of several RGB band combinations, we found that the 2, 5 and 7 give good discrimination between limestones, sandstones, and alluviums.…”
Section: Lithology Extraction and Mappingmentioning
confidence: 99%
“…This remote sensing technique is widely used in geological studies and involves a transformation of data by giving the numerical value of one band and dividing it by the numerical value of another band (Mars & Rowan, 2010;Pour & Hashim, 2012). The band ratio is chosen according to the absorption and reflection characteristics of a given target (Pour & Hashim, 2012;Tobi et al, 2022).…”
Section: Digital Image Pre-processing and Processingmentioning
confidence: 99%
“…The results indicate that (Table 3): 1) The average content of SiO 2 and CaO decreased significantly as the elevation increased; while the average content of Al 2 O 3 , Fe 2 O 3 , MgO, and Corg. showed an obvious upward trend (Mendes et al, 2022;Tobi et al, 2022); There is no clear linear relationship between the average content of Na 2 O and K 2 O and the elevation, and the maximum value occurs in the lower elevation range (Poppiel et al, 2020;Qi et al, 2021). 2) In terms of the relationship between soil oxide content and slope, the average content of SiO 2 and Fe 2 O 3 shows an obvious upward trend with the increase of slope; The average content of Al 2 O 3 decreased firstly and then increased; The average contents of MgO, Na 2 O, K 2 O, and Corg.…”
Section: Response Relationship Between Soil Oxide Content and Geomorp...mentioning
confidence: 99%
“…pH and soil oxides can undergo dissimilatory reduction reaction (Heller Pearlshtien and Ben-Dor, 2020), improving the absorption of soil silicon source (Rathod et al, 2016), regulate soil activity (Heller Pearlshtien and Ben-Dor, 2020), and participate in the nitrogen cycle (Dong et al, 2011). A series of new application achievements have been made in the prediction of heavy metal content in soil (Zabcic et al, 2014;Huang et al, 2021;Bouzidi et al, 2022;Tobi et al, 2022), extraction of organic matter content (Qi et al, 2021), and formulation of soil remediation plan (Velicogna et al, 2021) by analyzing the mechanism of pH according to these phenomena.…”
Section: Introductionmentioning
confidence: 99%